CHANGED MORPHOLOGICAL TISSUE GUMS AS CONSEQUENCE PREPARATION TEETH - N.V. Tsvetkova (Український стоматологічний альманах, 2018)
Introduction. In literature the question of injury of interdental gingival papillae by micropieces of grinding hard tissues of the tooth crown and micropieces abrasive material separated during grinding not find your coverage. However, as confirmed by research conducted by us and the nature of injuries and the dynamics of pathological changes in the structure of interdental gingival papillae from the first to the seventh day after grinding bits indicate the presence of acute inflammation or acute gingivitis.